Perbandingan Metode Simple Additive Weighting Dan Weighted Product Dalam Penilaian Kinerja Guru - Dimas Aulia Trianggana; Indra Kanedi; Bella Oktavia (Jurnal Media Infotama, 2022)
The teacher performance appraisal process is carried out through a manual assessment form which will then be given a value according to predetermined criteria. Comparative analysis of the Simple Additive Weighting and Weighted Product methods on teacher performance assessment data is carried out by comparing the final results obtained from the two methods. The analysis is carried out by looking at the number of criteria used, the processing time and also the ranking results. Based on the tests that have been carried out, the comparison results obtained in terms of processing time, the SAW method is faster than the WP method, and from the ranking results the SAW method and the WP method have the same value.